DOUBLE STATION OBSERVATION OF METEORS WITH LOW BASELINE IN MYKOLAIV - Kulichenko, M. O.; Shulga, O. V.; Shulga, O. V. (Одеські астрономічні публікації, 2017)
Results of single and double station observations of meteors using TV CCD techniques which were conducted in 2013-2016 in Mykolaiv astronomical observatory (RI MAO) are shown in the article.